Employee risk management : how to protect your business reputation and reduce your legal liability - Rideout, Helen (Business writer) (London ; Philadelphia : Kogan Page, 2014)
"Employee Risk Management presents a straightforward, legally-grounded process that will enable employers to identify, manage and reduce the potential threats that come with every employee - as well as with anyone else who works for the organization, including contractors, volunteers, interns and temps. Chapters cover everything from recruitment to the end of the employment relationship. Readers will learn how to protect against threats as diverse as: managing employee social media use in order to safeguard business reputation; the new problems that an ageing workforce will present over the coming years; and concerns about remote working such as reduced productivity, data security and data protection risks. This book is an essential handbook for HR professionals and senior managers. As well as offering an unbeatable practical guide to employee risk management, it will bring them up-to-date with cutting edge developments in risk culture"--
Keywords: Risk management; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Management; LAW / Labor & Employment; Print books